Individual and contextual predictors of young Ukrainian adults' subjective well-being during the Russian–Ukrainian war - Pavlova, Iuliia; Krauss, Steven; McGrath, Breeda; Cehajic‐Clancy, Sabina; Bodnar, Ivanna; Petrytsa, Petro; Synytsya, Tetiana; Zhara, Hanna (Wiley, 2023)
The Russian invasion of Ukraine is accompanied by horrific losses among civilians. This study investigates various individual (hope, optimism, resilience, post-traumatic growth, and coping strategies) and contextual predictors (experience of life under occupation, actively hostile home environment, and frequent moves) of subjective well-being among the youth living in Ukraine. A total sample of 593 students from several universities participated in the study using surveys that contained questions about sociodemographic characteristics, life satisfaction, hope, optimism, personal post-traumatic growth, resilience, and coping strategies. Data were analyzed using JAMOVI software. The level of dissatisfaction with their own lives was 34.7%; most of the respondents had a higher incidence of minimal/mild hopelessness (88.7%) and high/moderate level of optimism (60.9%). The majority of participants had moderate and high levels of post-traumatic growth (51.9% and 6.7%, respectively) and resilience (46.0% and 14.5%, respectively). Optimism, hope, resilience, post-traumatic growth, using emotional support, and life in occupation predicted life satisfaction among the study sample.